1988
DOI: 10.1295/polymj.20.107
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Chemical Shifts Calculation for Model Compounds of Ethylene–Propylene Copolymer with a Low Ethylene Content

Abstract: ABSTRACT:13 C NMR chemical shifts of the model compounds for ethylene-propylene (E-P) copolymer with a low ethylene content were calculated using the gamma-effect of 13 C chemical shift and Mark's rotational isomeric state matrices of E-P copolymer. The carbons of interest in the model compounds are included in the same monomer unit surrounded by different comonomer sequences due to the substitution of monomer unit between ethylene and propylene. Observed 13 C chemical shift differences for the carbons of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…-"0(5) ri_S7a|sa (10) mi-S7Q^ (13) ri-Sr"6i (20) m0-T«s(24) 34.2-34.8 -'1 ß(5) mi-ST"fli (10) -'µ« (17) mi-S7aSS (20) r0-Tai(24) -< ( 16)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-"0(5) ri_S7a|sa (10) mi-S7Q^ (13) ri-Sr"6i (20) m0-T«s(24) 34.2-34.8 -'1 ß(5) mi-ST"fli (10) -'µ« (17) mi-S7aSS (20) r0-Tai(24) -< ( 16)…”
Section: Resultsmentioning
confidence: 99%
“…This method is especially useful for the 13C NMR tacticity assignments of polyolefins and has been successfully applied to the tacticity assignment of the 13C NMR spectra of a series of linear polyolefins,1-8"16 poly-(3-methyl-l-butene),17 E-P copolymer,2-18"20 and B-P copolymer. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The additive rules for predicting the 13C NMR chemical shifts of methyl-substituted alkanes proposed empirically by Cheng and Bennett22-23 are also available for the assignments.…”
Section: Introductionmentioning
confidence: 99%
“…In the preceding paper, 19 we demonstrated that the chemical shifts due to the gamma-effect is sensitive to the displacement between the ethylene and propylene units. It has been confirmed that the chemical shift calculation via the gamma-effect is applicable to the pentad and hexad comonomer sequence assignments of methyl and methylene resonances in the 13 C NMR spectrum of stereoregular E-P copolymer.…”
Section: Resultsmentioning
confidence: 89%
“…The same procedure can be performed on the (mrr) fraction, giving (rrrm) + 2(mrrm) = (rmrr) + (mmrr) (4) Note that this also follows from Eq. 1) and (2), however, are added for explanation and allow generalization to hexads, heptads, etc.…”
Section: The Conservation Lawsmentioning
confidence: 92%